Multimorbidity and polypharmacy: a risk factor for older patients - Cucinotta, Domenico (Acta Biomedica Atenei Parmensis, 2022)
Invited commentary on Letter: Acta Biomed 2022; Vol. 93, N. 2: e2022136 DOI 10.23750/abm.v93i2.12855 https://mattioli1885journals.com/index.php/actabiomedica/article/view/12855